Folk Tourism and Deoghar, Jharkhand - R K , Archana Sada Suman Tudu; Sarma, Rabindranath (International Journal of Psychosocial Rehabilitation, 2020)
The state of Jharkhand is well-known for its sacred locations, hills, and waterfalls that are surrounded by magnificent hills, rivers, lakes, and a wide variety of plants and animals. The state has the potential to develop nationally and internationally significant pilgrimage attractions. In the state, religious tourism is the most prevalent kind of travel. The shrines receive a lot of visitors each year. Popular places of worship include Maa Ugratara Temple, Surya Mandir, Shakti Mandir, Sai Temple, Tuti Jharna Mandir, Bhairosthan Temple, Baidyanath Dham, Jagannath Mandir, Dhurwa, Rankini Mandir, and Sun Temple. The researcher attempts to provide some exploratory exposures and insights of Jharkhand with special reference to Deoghar district through this paper; however, it is completely theoretical in nature.